The Effect of Directed Reading Thinking Activity (DRTA) towards the Ability of Reading Understanding of Intellectual Disability Students in SDLB - Siti Pujiati; Mohamad Efendi; Saichudin Saichudin (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
Barriers in the cognitive processes stages make intellectual disability students have problems in reading comprehension. Directed Reading Thinking Activity (DRTA) which demands student activity during the learning process can be a solution to overcome the problem of the students’ reading understanding. The purpose of this study is to describe the effect of the DRTA usage towards the reading comprehension ability of intellectual disability students in SDLB. The method used is a quasi experiment with times series design. The results showed a significant increase (comparing mean pre-test = 69.4 and post-test value = 87), while significance value (2-tailed) was less than α. In conclusion, the use of DRTA has an effect on the reading comprehension of the intellectual disability students in SDLB.